“Take your time…” - Pobeguts, Sergey (project baikal, 2021)
The article concerns some peculiarities of A. Rappaport’s thinking: his commitment to unhurried consideration of any issue in general and architectural problematics in particular; his feeling of the necessity to go back to the origins of contemporary views of architecture to bring the lost spiritual and moral qualities back to architecture; his criticism of professional education as a set of renewable cliches.
Keywords: “other” ex multis; unhurried manner; “unfitness” of questions; spirituality; sincerity of feeling of architecture